MSP1 encodes an essential RNA-binding pentatricopeptide repeat factor required for nad1 maturation and complex I biogenesis in Arabidopsis mitochondria - Best, Corinne (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.